The effects of indole butyric acid and seaweed (Posidonia oceanic) and their mixture in improving photosynthetic pigments of salt-stressed wheat cultivar (Marjawi). - salih, sami; Amrajaa Abdulrraziq, Ahmed (Scientific Journal for Faculty of Science-Sirte University, 2023)
Salt stress is one of the most limiting factors in the production of agricultural crops. This study was conducted to test the effect of different salinity levels at concentrations (0.0, 100, 200, and 300 mM) of sodium chloride on the photosynthetic pigments content of Triticum aestivum (Marjawi cultivar), and attempting to treat using several transactions of different treatments, include: spraying at 100 mg/L of Indole3- Butyric Acid (seedlings 2 weeks old), adding crude powder of seaweed Posidonia oceanica 25 g/pot (before agriculture), and (mixture) of a crude powder of P.oceanic 25 g/pot + spraying IBA, with three replications according to a completely randomized design. The results showed a significant decrease in the content of chlorophyll (a, b), carotenoids, and Total pigments with increasing NaCl concentrations, compared to a control. Moreover, spraying with (IBA) decrease significantly the negative effect of salinity. Also result indicated that adding crude powder of P.oceanica was not successful in reducing salt stress, in addition, the result showed that the mixture was superior in recording the best rates in improving the photosynthetic pigments content of wheat salt-stressed, This study concluded that harmful effects of salinity can be mitigated using the mixed treatment.